Want this question answered?
Be notified when an answer is posted
2n+4/2 term 1 = 3 term 2 = 4 term 3 = 5 term 4 = 6
2n+3. If 5 is the first term, then it is 2n + 3 (2×1 = 2 + 3 = 5 and 2×2 + 3 = 7)
The nth term is: 5-2n
The Nth term of tn = 2n + 3 is 2N + 3. Replace (substitute) the n by the term number to get its value. t1 = 2 x 1 + 3 = 5 t2 = 2 x 2 + 3 = 7 t3 = 2 x 3 + 3 = 9 etc.
It is: 2n+4
2n-1 to the tenth term = 1
3=2n
The nth term is: 2n+7 and so the next number will be 19
The nth term of the sequence 2n + 1 is calculated by substituting n with the term number. So, the tenth term would be 2(10) + 1 = 20 + 1 = 21. Therefore, the tenth term of the sequence 2n + 1 is 21.
The nth term of the sequence is 2n + 1.
Un = 2n - 8 Un = 2n - 8 Un = 2n - 8 Un = 2n - 8
The nth term is 2n+5 and so the next number is 17
n = 1, 2n = 2 n = 2, 2n = 4 n = 3, 2n = 6 2, 4, 6, ..., 2n where n = 1, 2, 3, ... This is an arithmetic sequence, where the first term is 2 and the common difference is 2.
151
Each number in this sequence is twice the previous number. The nth. term is 2n-1.Each number in this sequence is twice the previous number. The nth. term is 2n-1.Each number in this sequence is twice the previous number. The nth. term is 2n-1.Each number in this sequence is twice the previous number. The nth. term is 2n-1.
2n+4/2 term 1 = 3 term 2 = 4 term 3 = 5 term 4 = 6
41.